Evaluación técnico-económica de la implementación de equipos de refrigeración domésticos alimentados con energía solar en la ciudad de Barranquilla (2021)
An investigative study was carried out in order to determine if an air conditioning adapted to work from photovoltaic energy with solar panels can be more efficient compared to one powered by the electrical network, for this they will be investigated in databases and studied In the implementations, what factors can favor it, taking into account very specific characteristics such as costs, life time, equipment power, etc. selected the most suitable for the project which was RECREATE. Based on this equipment, thermodynamic calculations were made based on the vapor compression cycle which showed us that the COP is equal to 3.9. Based on the COP value, the technical installation and investment values of the SOLAR KIT were obtained, which was approximately $ 11,000,000 COP. Finally, the cost calculations showed that the implementation of the cooling system with solar panels will have an TIR of 5.7 years, which indicated that it is a viable project